Analysis of PJOK teacher competency, Physical Fitness and Academic Achievement of Class XII Students at SMAN 1 Mantup Lamongan: Analisis kompetensi guru PJOK, Kebugaran Jasmani dengan Prestasi Akademik Siswa kelas XII di SMAN 1 Mantup Lamongan - Efendi, Rahmat; Kristiyandaru, Advendi; Hidaya, Taufiq (Jurnal Porkes, 2024)
This study aims to analyze the relationship between teacher competence, physical fitness, and academic achievement of class XII students at SMAN 1 Mantup Lamongan. This type of research is correlational. The population in this study was 229 students of SMAN 1 Mantup Lamongan. The sample used was 65. Data analysis using validity test, reliability test, pre-requisite test and hypothesis testing using R test and F test. Data collection techniques using progressive aerobic cardiovascular endurance run. The results of the study are the analysis of the relationship between teacher competence and academic achievement obtained sig value < 0.20, < 0.05, so it can be concluded that there is a relationship between teacher competence and academic achievement, analysis of the relationship between physical fitness and academic achievement obtained sig value < 0.03, < 0.05, so it can be concluded that there is a relationship between physical fitness and academic achievement, analysis of the relationship between teacher competence, physical fitness with academic achievement obtained sig value < 0.002, < 0.05, so it can be concluded that there is a simultaneous relationship between teacher competence, physical fitness with academic achievement.